Percepção dos discentes do curso de ciências contábeis quanto à importância do conhecimento em contabilidade tributária. - Fonseca, Marco Antonio Lemos da (2017)
This paper aims to measure the importance of knowledge in Tax Planning for the students of the Accounting Sciences course in order to identify whether, when comparing the students’ perception of from 1st to 10th periods of the course, the level of knowledge on the subject is higher among the graduates. The objective of the research was, therefore, to make a survey and analyze the students' understanding of Accounting Sciences about Tax Planning. To achieve this goal we carried out a descriptive study with a quantitative approach, with the data collected through a questionnaire prepared by the author containing 20 questions, which was applied in a higher education institution, answered by 533 students from all periods, integral and nocturnal. An identification of the profile of these students quantitatively and dealings of the conceptual aspects according to the average of the grades given by the respondents in question numbers 14 to 20 of the questionnaire was performed. There was a small divergence of opinions between students from the same period of different shifts and a greater distancing when comparing incoming students (1st period) and graduates (10th period). It was concluded that this greater divergence is explained in part by the fact that the graduates have more professional and academic experience, while most freshmen do not yet have experience in accounting. However, there were involution of some concepts, which would be explained by possible problems in the teaching.